The Radio Girls on the program - Penrose, Margaret; Gooch, Thelma, 1895-1973 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Radio Girls on the Program: or Singing and Reciting at the Sending Station" by Margaret Penrose is a work of juvenile fiction likely written in the early 20th century. The story revolves around the adventures of high school girls Jessie Norwood and Amy Drew as they navigate friendships, competition, and the world of radio broadcasting during a summer filled with excitement. The opening of the book introduces us to Jessie and Amy as they discuss an unpleasant encounter with a girl named Belle Ringold, showcasing their dynamic and playful friendship. As they walk home, discussing an upcoming radio concert, an unexpected event occurs when an aviator crashes his plane nearby, providing a dramatic twist. This incident quickly shifts their focus as they rush to help the injured pilot, revealing their courage and resourcefulness. The beginning sets the tone for a captivating blend of youthful adventure and budding interests in radio technology, while also hinting at tensions with rivals and the complexities of adolescent relationships. (This is an automatically generated summary.)
Originally published by Cupples & Leon Company, Publishers, Margaret Penrose's "Radio Girls" books were later published by The Goldsmith Publishing Co. as "Campfire Girls" books, without illustrations. This book was also published as: The Campfire Girls on the program; or, Singing and reciting at the sending station.
Release date is 2023-03-31
Bob Taylor, David Edwards and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Adventure stories; Girls -- Societies and clubs -- Juvenile fiction; Fund raising -- Juvenile fiction; Radio broadcasting -- Juvenile fiction; Singing -- Juvenile fiction